The Effect of Arrive Angle of External Magnetic Field on The Shape of Hysteresis Curve Permalloy Ni80Fe20 By Simulation - Lestari, Merinda; Nursiyanto, Widia; Nugroho, Agung Tjahjo (Physics Department, Faculty of Mathematics and Natural Sciences, University of Jember, 2021)
Magnetic sensor is a type of sensor that utilizes changes in resistance caused by changes in the magnetic field H or B. One of the suitable magnetic materials to be used as a study material for making magnetic sensors is permalloy Ni80Fe20. The reading error of the magnetic sensor of the Ni80Fe20 permalloy material affects hysteresis curve of the material and requires correction of the angle of incidence of the external magnetic field in order to provide accurate results on the storage media. In this our current research using Finite Difference OOMMF, we investigated the effect of the angle of incidence of the external magnetic field (H) on the hysteresis curve was carried out on an application based on. The research was conducted by reviewing the parameter literature of the Ni80Fe20 permalloy material and then compiling it in a script and simulating it on an application based on Finite Difference OOMMF. The data obtained from the simulation are normalized magnetization (m), external magnetic field H and coercivity field (Hc) which have been influenced by the angle of incidence. The results of the hysteresis curve at a size of 5 nm with a variation of the angle of incidence 0o are indicated by the value of the external magnetic field H of 10000 mT to -10000 mT with a coercive field Hc of 5000 mT to -5000 mT. The normalized magnetization value m is 1 to -1. The variation of the angle of incidence of 30o produces a coercive field Hc of -108.3 mT to 108.3 mT and a normalized magnetization of 0.86 to -0.86. The 45o incident angle variation produces a coercive field Hc -88.4 mT to 88.4 mT and a normalized magnetization of -0.7 to 0.7